2021
DOI: 10.1186/s12872-021-01948-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum alanine aminotransferase and hypertension: A national based cross-sectional analysis among over 21 million Chinese adults

Abstract: Background Inconsistent results were found in the association between serum alanine aminotransferase (ALT) and hypertension among population-based studies. This study evaluated the association between ALT and hypertension among Chinese reproductive-age population by utilizing registration data from National Free Pre-pregnancy Checkups Project in 2016–2017. Methods The 21,103,790 registered participants were eligible for analysis, including women wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…For GGT, in the highest quartile group compared with the lowest quartile, the multivariate-adjusted OR for hypertension was 2.29 (1.68–3.14) in males and 1.52 (1.27–1.83) in females [ 3 ]. In agreement with the results of our study, some previous studies also showed that increased levels of ALP [ 10 12 ], GGT [ 8 , 10 ], ALT [ 10 , 25 , 26 ], and AST [ 25 , 27 ] within the normal range are associated with the odds of hypertension. For early detection of nonliver-related disorders such as hypertension, it seems logical that the cutoff level of serum ALT, AST, GGT, and ALP concentrations is modified at a lower level.…”
Section: Discussionsupporting
confidence: 93%
“…For GGT, in the highest quartile group compared with the lowest quartile, the multivariate-adjusted OR for hypertension was 2.29 (1.68–3.14) in males and 1.52 (1.27–1.83) in females [ 3 ]. In agreement with the results of our study, some previous studies also showed that increased levels of ALP [ 10 12 ], GGT [ 8 , 10 ], ALT [ 10 , 25 , 26 ], and AST [ 25 , 27 ] within the normal range are associated with the odds of hypertension. For early detection of nonliver-related disorders such as hypertension, it seems logical that the cutoff level of serum ALT, AST, GGT, and ALP concentrations is modified at a lower level.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, dietary IA supplementation significantly increased SOD and CAT contents in the serum at d 1 to 21 and T-AOC at d 22 to 42, indicating that IA can help reduce oxidative stress. Aminotransferases, including ALT and AST, are well-known markers for liver injury ( Jia et al, 2021 ). A growing body of evidence strongly suggests that higher serum ALT or AST levels are substantially correlated with increased liver fat accumulation and excessive inflammation ( Feng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The population in our study was mainly composed of patients with NAFLD, so the predictor ALT is included. A few studies have explored the association between ALT and HBP development, with equally few studies demonstrating association between ALT and HBP [53,54,55] . One of the cross-sectional studies conducted in Chinese adults suggested a positive linear correlation between ALT and HBP development.…”
Section: Model Evaluation and Comparisonmentioning
confidence: 99%